Effect of long distance transport on farm fresh tomatoes - Goyal, R K; Kumar, Dilip; Walia, Himanshu; Kumar, Pushpinder (Journal of Agricultural Engineering, 2005)
Fresh tomatoes of Avinash-2 variety at pink and breaker stage were transported for distance of 400 km. Three types of packaging mediums namely Plastic crates, Corrugated fibre board boxes and wooden boxes were used. The cushioning materials used were grass, paper and straw. The overall minimum damage was recorded in T1 (Breaker: Plastic crate: Grass) i.e. 3.93% followed by T8 (Breaker: Wooden: Paper) i.e. 4.10% and T9 (Breaker: Wooden: Straw) i.e. 4.38%. The overall mean damage (%) for wooden box was significantly lesser than plastic crates (9.83%) Â·and corrugated fibreboard box (10.98%).